Desain dan Pengembangan Media Pembelajaran Berbasis Mobile Menggunakan Pendekatan Demonstrasi Interaktif untuk Pendidikan Desain Grafis - Muhammad Amin Rais; Mutiara Akbar Nasution; Rahman Wahabi Hasibuan (Jurnal Sains, Teknologi & Komputer, 2024)
This study aims to develop a mobile-based graphic design learning media using the Interactive Demonstration approach and to evaluate its feasibility and effectiveness in improving students’ learning outcomes. The study employed a Research and Development (R&D) method using the Agile development model, which consists of requirements analysis, design, development, testing, and deployment. The product was implemented for Grade XI Graphic Design students at SMK Negeri 13 Medan. Product quality was evaluated through material expert validation, media expert validation, user acceptance testing, and Blackbox testing, while its effectiveness was measured using a pretest–posttest design analyzed through an Independent Samples t-test. The results indicate that the developed Android-based learning media functions properly across different devices and provides interactive features that support graphic design learning. Expert validation and user acceptance demonstrated that the media achieved a very high level of feasibility. Furthermore, students who used the mobile learning media achieved significantly higher learning outcomes than those who learned using conventional modules. These findings suggest that mobile-based learning media integrated with the Interactive Demonstration approach is both feasible and effective for supporting graphic design instruction in vocational education.